US power sector carbon capture and storage under the Inflation Reduction Act could be costly with limited or negative abatement potential. (10th March 2023) - Grubert, Emily; Sawyer, Frances
Abstract: The United States' (US) largest-ever investment in expected climate mitigation, through 2022's Inflation Reduction Act (IRA), relies heavily on subsidies. One major subsidy, the 45Q tax credit for carbon oxide sequestration, incentivizes emitters to maximize production and sequestration of carbon oxides, not abatement. Under IRA's 45Q changes, carbon capture and storage (CCS) is expected to be profitable for coal- and natural gas-based electricity generator owners, particularly regulated utilities that earn a guaranteed rate of return on capital expenditures, despite being costlier than zero-carbon resources like wind or solar. This analysis explores investment decisions driven by profitability rather than system cost minimization, particularly where investments enhance existing assets with an incumbent workforce, existing supplier relationships, and internal knowledge-base. This analysis introduces a model and investigates six scenarios for lifespan extension and capacity factor changes to show that US CCS fossil power sector retrofits could demand 0.4–3.6 trillion in 45Q tax credits to alter greenhouse gas emissions by −24% (0.4 trillion) to +82% (3.6 trillion) versus business-as-usual for affected generators. Particularly given long lead times, limited experience, and the potential for CCS projects to crowd or defer more effective alternatives, regulators should be extremely cautious about power sector CCS proposals.